Critical aspect of renewable syngas production for power-to-fuel via solid oxide electrolysis: Integrative assessment for potential renewable energy source. (June 2022) - Choe, Changgwon; Cheon, Seunghyun; Gu, Jiwon; Lim, Hankwon
Abstract: In this work, an integrative assessment of renewable syngas production by solid oxide electrolysis (SOE), which is also called co-electrolysis, was performed to investigate economic and environmental viability based on various renewable energy resources. First of all, economic analysis using itemized cost estimation, predictive cost assessment, and uncertainty analysis through Monte-Carlo simulation was carried out for estimating current and future levelized cost of syngas and possible cost ranges of the syngas production. From these analyses, the economic competitiveness of syngas production can be achieved with simultaneous cost reduction of major economic parameters, such as SOE system cost, CO2 price, and levelized cost of electricity. Furthermore, the low environmental potential of syngas production using some of the renewable energy sources was proved through life-cycle assessment. Finally, analytic hierarchy process was implemented to determine which one is the most feasible renewable energy in the technical, economic, and environmental aspects simultaneously. As a result, renewable syngas production coupling SOE and onshore wind electricity can bring considerable benefits in terms of CO2 utilization and other value-added chemical production. Highlights: Integrative assessment of electrochemical syngas production was carried out. Various renewable energy resources were considered with solid oxide electrolysis. Cost estimation and life-cycle assessment were performed for all energy resources. Analytic hierarchy process was conducted to detect the most viable renewable energy.